MazEF Toxin-Antitoxin System-Mediated DNA Damage Stress Response in Deinococcus radiodurans - Dai, Jingli; Chen, Zijing; Hou, Jinfeng; Wang, Yudong; Guo, Miao; Cao, Jiajia; Wang, Liangyan; Xu, Hong; Tian, Bing; Zhao, Ye (Frontiers in Genetics, 2021)
Deinococcus radiodurans shows marked resistance to various types of DNA-damaging agents, including mitomycin C (MMC). A type II toxin-antitoxin (TA) system that responds to DNA damage stress was identified in D. radiodurans, comprising the toxin MazF-dr and the antitoxin MazE-dr. The cleavage specificity of MazF-dr, an endoribonuclease, was previously characterized. Here, we further investigated the regulatory role of the MazEF system in the response to DNA damage stress in D. radiodurans. The crystal structure of D. radiodurans MazF (MazF-dr) was determined at a resolution of 1.3 Å and is the first structure of the toxin of the TA system of D. radiodurans. MazF-dr forms a dimer mediated by the presence of interlocked loops. Transcriptional analysis revealed 650 downregulated genes in the wild-type (WT) strain, but not in the mazEF mutant strain, which are potentially regulated by MazEF-dr in response to MMC treatment. Some of these genes are involved in membrane trafficking and metal ion transportation. Subsequently, compared with the WT strain, the mazEF mutant strain exhibited much lower MMC-induced intracellular iron concentrations, reactive oxygen species (ROS), and protein carbonylation levels. These results provide evidence that MazEF-mediated programmed cell death in D. radiodurans might be caused by an increase in ROS accumulation upon DNA damage stress.